PEMAPARAN KRIMINALITAS DAN BUDAYA SIBER MELALUI SEMINAR LITERASI DIGITAL KEPADA MASYARAKAT DESA CIELA - Elsen, Rickard; Ramadhan, Muhammad Rizky; Nuraeni, Intan; Nurfitri, Lulu Bintang; Anwari, Aldi Yunan; Hoeriah, Dea Nurul; Melinda, Zihan; Ismail, Ridwan; Ruslam, Alam; Fauziyah, Adinda Jaida; Indrakusumah, Muhammad Rafi; Rodiansyah, Novan; Gumilar, Ari Fajar; Setiaji, Bayu; Fatmawati, Alya; Syafei, Fikri Ramdani Abdullah; Fauzan, Muhammad Alwan; Fajriyanti, Neng Nenti; Banowati, Rika (Jurnal PkM MIFTEK, 2024)
The development of technology and information has brought various impacts in human life. Especially for the younger generation who were born and grew up in the development of technology. The reading ability of the internet generation (net generation) needs to be directed towards an understanding of digital information and the utilization of various digital media platforms. Digital literacy is a person's ability or skill to understand and use information from various digital sources. The purpose of writing this article is to see the challenges faced and how people should respond to hoax news in digital media with the ease and speed of internet access and the uncontrolled use of social media so that it is difficult for us to find the truth when we have the inability to choose and sort information, so that we can become a true generation that is not only able to face the changes and developments of the times. The method used in writing this article is the literature review method by using literature in the form of books, journals, notes, or reports on previous research results. Training and socialization efforts such as digital literacy seminars and door to door digital literacy are expected to help the younger generation and society as a whole become wiser in dealing with digital information, avoid hoaxes, and make positive use of technology.